2013
DOI: 10.1111/hiv.12011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of switching from zidovudine/lamivudine to tenofovir/emtricitabine on lipoatrophy: the RECOMB study

Abstract: ObjectivesLipoatrophy is a long-term adverse effect of some antiretrovirals that affects quality of life, compromises adherence and may limit the clinical impact of HIV treatments. This paper explores the effect of tenofovir/emtricitabine (TDF/FTC) on the amount of limb fat in patients with virological suppression. MethodsA randomized, prospective clinical trial was performed to compare continuation on a zidovudine/lamivudine (ZDV/3TC)-based regimen with switching to a TDF/FTC-based regimen in terms of the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…One limitation of our study is the small sample size, which may have compromised our results. Nevertheless, this was a subanalysis of a study designed as a pilot, exploratory trial with a sample of 80 subjects (40 in each arm) , of whom 15 were women who were excluded from our sample, and even with this sample size we were able to find statistically significant differences between and within groups.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One limitation of our study is the small sample size, which may have compromised our results. Nevertheless, this was a subanalysis of a study designed as a pilot, exploratory trial with a sample of 80 subjects (40 in each arm) , of whom 15 were women who were excluded from our sample, and even with this sample size we were able to find statistically significant differences between and within groups.…”
Section: Discussionmentioning
confidence: 98%
“…The RECOMB study has been described elsewhere . In summary, it was a controlled, multicentre, open‐label, randomized clinical trial in virologically suppressed HIV‐1‐infected adults, comparing the impact of switching from ZDV/3TC to FTC/TDF versus continuing on ZDV/3TC on total limb fat mass assessed by DEXA over a 72‐week period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher SAT density in tNRTI-exposed persons may represent lipoatrophic AT with decreased adipocyte size and increased fibrosis, macrophage infiltration and inflammation (18,38). Although switching from a tNRTI-based ART regimen to abacavir-or tenofovir-containing regimens has led to some improvement in limb fat quantity as measured by dual-Xray absorptiometry (39,40,41), higher SAT density after controlling for SAT quantity suggests that the detrimental AT effects of tNRTI exposure are incompletely reversible (42,43). Although observational studies have found that d4T is associated with a greater risk of SAT loss than AZT (44), given the high rate of mixed tNRTI exposure in our cohort we did not evaluate the effects of these agents on SAT quality individually.…”
Section: Discussionmentioning
confidence: 99%
“…However, substantial progress has been made in understanding pathogenic mechanisms such as host genetic determinants, the impact of HIV infection per se, and the role of antiretroviral therapy. Spanish researchers contributed significantly to characterizing the role of distinct drugs and ways to prevent it [ 50 , 51 ].…”
Section: Lipodystrophy Metabolic Abnormalities and Cardiovasculamentioning
confidence: 99%